THE SIGNIFICANCE OF THE UZBEK LANGUAGE NOW - Mohinur Toshboyeva Soatmurod qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In the article, the importance of our Uzbek language in today’s world understandings about the place in society and the biggest place in our lives given.